Enterocele Presenting as Anterior Rectal Prolapse: Resolution with Vaginal Repair. (3rd January 2020) - Towers, Geoffrey D.; Benoit, Candace; Maxwell, Rose; Yaklic, Jerome
Abstract : An enterocele is a pelvic hernia formed from the separation of endopelvic fascia, associated with the posterior or anterior vaginal fornix, and most commonly located in the posterior superior vaginal segment. Rectal prolapse is a debilitating condition in which the mucosa of the rectum protrudes circumferentially from the anus. Surgical repair is the recommended treatment for rectal prolapse, and though there are many different surgical options, there is no consensus on which approach is best. We present a case of anterior rectal prolapse due to enterocele which was treated by correction of enterocele with a vaginal approach and propose some clinical features and diagnostic techniques that may distinguish this entity from traditional rectal prolapse.